2007
DOI: 10.1111/j.1444-2906.2007.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into nucleotide and Ca2+binding to carp ?-actin

Abstract: Nucleotides and Ca 2+ binding to a-actin prepared from ordinary skeletal muscle of carp Cyprinus carpio was studied. When bound Ca 2+ was removed with ethylenediaminetetraacetic acid, carp a-actin denatured more rapidly than chicken a-actin. Kinetic studies of the denaturation process showed that in the absence of divalent cations, the binding constants of ATP to carp and chicken actin were 5.0 ¥ 10 4 /M and 1.2 ¥ 10 5 /M, respectively. Competitive binding of Ca 2+ between actin and 8-amino-2-[(2-amino-5-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The difference in thermal stability between these two actins is more pronounced than for G-actins [4]. This is somewhat confusing given that the instability of carp G-actin results from having a low affinity for nucleotides [4,5]. In F-actins, the bound nucleotide cannot be exchanged with free nucleotide in a solution [19].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The difference in thermal stability between these two actins is more pronounced than for G-actins [4]. This is somewhat confusing given that the instability of carp G-actin results from having a low affinity for nucleotides [4,5]. In F-actins, the bound nucleotide cannot be exchanged with free nucleotide in a solution [19].…”
Section: Discussionmentioning
confidence: 93%
“…The substitution at the 155th position (Ala-155 in carp and Ser-155 in chicken actin) is located in a b-hairpin (Asp154-His161) of the nucleotide binding region, which sandwiches bound nucleotide together with another b-hairpin, Asp11-Lys18 [1]. It has been shown that the Ala-155 is an almost unique substitution that affects the nucleotide binding of carp G-actin [5,21]. Therefore, the open conformation of the nucleotide binding region in carp F-actin and the resulting thermal instability will be due to the substitution.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The fact suggests that affinity of ATP for fish actin is lower than that for actin from terrestrial animals. Ooi and Soematsu demonstrated that this is the case for carp α‐actin by directly comparing nucleotide binding between carp and chicken actin 13 . In addition, Ooi and Soematsu showed that affinity of Ca 2+ for carp actin was also lower than that of chicken actin 13 …”
Section: Introductionmentioning
confidence: 98%